Profil Kepercayaan Diri Akademik Siswa Kelas X SMA Plus Al-Aqsha Cibeusi Tahun Ajaran 2023/2024 - Andriani, Dewi; Thahir, Muthahharah; Rayaginansih, Syari Fitrah (Jurnal Dimamu, 2025)
This study is motivated by low academic self-confidence which can reduce students' learning motivation in completing school assignments. The purpose of this study was to determine the description of academic self-confidence of grade X students of SMA Plus Al-Aqsha Cibeusi in the 2023/2024 school year. The study used a descriptive quantitative approach with a population of all X grade students totaling 136 students. The sampling technique used saturated samples, so that the entire population was sampled. Data collection is done through observation, interviews, and distribution of self-confidence instruments with a Likert scale. The validity test was carried out on 54 items and obtained 31 valid questions using the Product Moment formula with a significance of 5%. Reliability test using Cronbach's Alpha coefficient obtained a value of 0.719, indicating a reliable instrument. Normality test using Kolmogorov-Smirnov showed a significance of 0.613, so the data was normally distributed. Data analysis used descriptive statistics with frequency distribution to categorize self-confidence in the high, medium, and low categories. The results showed 16 students (12%) were in the high category, 119 students (88%) in the medium category, and 1 student (1%) in the low category.